2014
DOI: 10.1136/bjophthalmol-2013-304485
|View full text |Cite
|
Sign up to set email alerts
|

A prospective and nationwide study investigating endophthalmitis following pars plana vitrectomy: incidence and risk factors

Abstract: Background/aims This is the first nationwide prospective study to investigate the incidence and risk factors of endophthalmitis following pars plana vitrectomy (PPV). Methods This was a prospective, nationwide casecontrol study. Cases of presumed infectious endophthalmitis within 6 weeks of PPV were reported via the established British Ophthalmological Surveillance Unit. The surveillance period was 2 years. Controls (patients who had PPV but no endophthalmitis) were recruited from nine randomly selected UK cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 20 publications
0
44
1
1
Order By: Relevance
“…Our observed rate of postvitrectomy endophthalmitis is similar to the one reported in the UK nationwide surveillance study at 0.058%. 12 Various risk factors have been proposed to be responsible for endophthalmitis after PPV. One important factor is inadequate wound closure in sutureless PPV surgeries due to a propensity for wound leak and subsequent intraocular ingress of surface microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our observed rate of postvitrectomy endophthalmitis is similar to the one reported in the UK nationwide surveillance study at 0.058%. 12 Various risk factors have been proposed to be responsible for endophthalmitis after PPV. One important factor is inadequate wound closure in sutureless PPV surgeries due to a propensity for wound leak and subsequent intraocular ingress of surface microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research found that rates were increased in smaller-gauge surgery [30]. However, more recent and larger studies have found no significant difference in the rate of endophthalmitis with smaller-gauge surgery [31,32]. It is likely that these differing conclusions reflect the evolution of small-gauge surgery: improving surgical technique and advancing technology have perhaps resulted in a decreasing incidence of endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…The patient had a pre-PPV visual acuity of 6/9, which worsened after the endophthalmitis to 6/24 at 9 months partially limited by the nuclear sclerotic cataract. Similarly, Park et al 42 have published a large, prospective nation-wide study looking at endophthalmitis after PPV in UK. In their series, 28 out of a total of 48 433 eyes (1 in 1730) undergoing vitrectomy developed endophthalmitis.…”
Section: Floaters-only-vitrectomy Recently Sebag Et Almentioning
confidence: 98%
“…21 Similarly, there have been two separate reports of endophtalmitis following PPV for floaters as well. 41,42 Table 1 summarises all the major studies on PPV for SVO.…”
Section: Summary Of Various Studies On Ppv For Svomentioning
confidence: 99%